2013
DOI: 10.1007/s13197-013-1172-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of gum tragacanth as bind enhancing agent in extended restructured mutton chops

Abstract: Use of extenders in meat products is not only health promoting but can also increase the economic worth of the products. Extension of the meat product is generally associated with poor binding and texture. Thus, the present study was envisaged to solve this problem by the incorporation of gum tragacanth (GT) as bind enhancing agent, used at three different levels viz., 0.1, 0.15 and 0.2 % in a pre standardized formulation of extended restructured mutton chops (ERMC), by replacing the lean meat. The products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
3
7
1
Order By: Relevance
“…Further, good hygienic and sanitation practices followed while handling, processing and packaging of the cooked products could also account for the absence of coliforms. Similar results were reported by Sharma et al (2013) in restructured mutton chops and Kumar et al (2015) in meat spread.…”
Section: Coliformssupporting
confidence: 88%
See 2 more Smart Citations
“…Further, good hygienic and sanitation practices followed while handling, processing and packaging of the cooked products could also account for the absence of coliforms. Similar results were reported by Sharma et al (2013) in restructured mutton chops and Kumar et al (2015) in meat spread.…”
Section: Coliformssupporting
confidence: 88%
“…Control products showed significant decrease (P \ 0.01) in juiciness at each interval of storage period and scores of T-1 and T-2 products were significantly lower (P \ 0.05) from 10th day onwards of storage period to respective initial score of these products. Loss of moisture occurring during aerobic storage of the product might have resulted in decreased juiciness of products Similar results were reported by Ahamed et al (2007), Sharma et al (2015) and many others. After taste score declined significantly (P \ 0.01) from 5th day onwards.…”
Section: Sensory Qualitysupporting
confidence: 86%
See 1 more Smart Citation
“…No significant difference (P [ 0.05) was observed even among treatments. Decreased appearance of the products could be due to some surface dehydration in aerobic packaging (Sharma et al 2015). With progressive storage, significant decrease (P \ 0.05) in flavour scores of control and treatment products was observed from day 3 and day 5 onwards, respectively.…”
Section: Sensory Scoresmentioning
confidence: 99%
“…Candogan and Kolsarici (2003a, b) reported that no difference in the protein content of low fat frankfurters containing fat replacers like carrageenan. Sharma et al (2015) also observed no significant difference (P [ 0.05) in any of the physicochemical parameters in restructured mutton chops incorporated with different levels of gum tragacanth except fat percent.…”
Section: Physico-chemical Propertiesmentioning
confidence: 81%